Ortner Syndrome: a rare cause of dysphonia - de Sousa, Mafalda (2021)
Ortner’s syndrome is a rare entity, characterized by dysphonia caused by recurrent laryngeal nerve (RLN) palsy, secondary to cardiovascular disorders. This work reports two cases of Ortner’s Syndrome. A 81-year-old male presented with dysphonia for a week. Physical examination showed left vocal fold palsy. Computed tomography (CT) revealed left atrial dilation. A 76-year-old male, had complaints of dysphonia for two weeks. Left vocal fold paralysis was observed. CT showed an aortic arch aneurysm. RLN is responsible for the innervation of the intrinsic laryngeal muscles, with exception of the cricothyroid muscle. Unilateral RLN palsy usually causes hoarseness. Bilateral RLN paralysis may be associated with more severe symptoms, such as dyspnea and stridor. Many benign and malign causes can affect the nerve through its course, whereby imaging is crucial in differential diagnosis. Despite being rare, Ortner’s syndrome may be the cause of vocal fold paralysis.